2005
DOI: 10.1007/s00261-005-0336-2
|View full text |Cite
|
Sign up to set email alerts
|

Expanded PTFE-covered stent-grafts in the treatment of transjugular intrahepatic portosystemic shunt (TIPS) stenoses and occlusions

Abstract: TIPS revision using the VIATORR endoprosthesis appears to be an effective and durable method to control shunt dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Covered stents have primary patency rates of 76–89% and 1 year shunt dysfunction of up to 15% (Table ) . TIPSS revision using the covered Viatorr endoprosthesis(Gore Medical) was found to be an effective and durable method of controlling shunt dysfunction .…”
Section: Complications Of Tipssmentioning
confidence: 99%
“…Covered stents have primary patency rates of 76–89% and 1 year shunt dysfunction of up to 15% (Table ) . TIPSS revision using the covered Viatorr endoprosthesis(Gore Medical) was found to be an effective and durable method of controlling shunt dysfunction .…”
Section: Complications Of Tipssmentioning
confidence: 99%
“…In addition, various experimental and clinical studies have verified the application of ePTFE-covered stent-grafts in de novo TIPS creation and TIPS revision (5, 8, 21, 24, 25). The ePTFE is utilized as a cover material for the stent-grafts, separating the blood flow within the shunt from the liver parenchyma and from the injured outflow hepatic vein.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, some investigators have described a combined transjugular and transhepatic approach. After puncturing the stent lumen transhepatically, a guidewire is passed through the shunt and snared through the internal jugular access (21, 22). Considering the improvement of surveillance methods and the multiple interventional techniques used for TIPS revision, the number of patients undergoing the PS creation has decreased gradually.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data on this, but Jirkovsky et al [27] showed that revising TIPS stenoses with a stent-graft specifically designed for TIPS led to better patency than did either angioplasty alone or stenting with a bare metal stent. A small study that used Viatorr devices for TIPS revision showed 1-and 2-year primary patency rates of 100% and 89%, respectively [28].…”
Section: Managing Tips Dysfunctionmentioning
confidence: 99%